Timing of GLP-1 Receptor Agonist Initiation for Treatment of Type 2 Diabetes in the UK - Kristina S. Boye; Dara Stein; Louis S. Matza; Jessica Jordan; Ren Yu; Kirsi Norrbacka; Syed Wasi Hassan; Luis-Emilio (Adis, Springer Healthcare, 2019)
Abstract Introduction Patients with type 2 diabetes mellitus (T2DM) who fail to meet glycaemic control are at increased risk of diabetes complications. For patients who cannot maintain glycaemic control with oral medication, one recommended option is to add an injectable glucagon-like peptide-1 receptor agonist (GLP-1 RA) to their treatment regimen. The purpose of this study was to examine time to treatment intensification with GLP-1 RAs, including the duration of time that patients did not maintain glycaemic control with oral medication. Methods This was a medical record review conducted in the UK via a physician survey. Patients eligible to have their records reviewed were required to be ≥ 18 years of age, have a confirmed T2DM diagnosis, and have initiated GLP-1 RA treatment for T2DM in the past 6 months. All glycated haemoglobin (HbA1c) values within 5 years prior to GLP-1 RA initiation were collected. Results A total of 113 physicians contributed data for 1096 patients (mean age at the time of GLP-1 RA initiation was 54.9 years, 55.4% were male, and 71.4% were White). Median time from T2DM diagnosis to GLP-1 RA initiation was 6.1 years. Median consecutive time patients taking oral regimens were not under glycaemic control (HbA1c > 7.0%) prior to GLP-1 RA initiation was 13.5 months. Patients treated by general practitioners (GPs) had a significantly longer duration of time with insufficient glycaemic control prior to GLP-1 RA initiation compared with patients treated by diabetes specialists (median time for specialists was 11.0 months vs. 17.0 months for GPs; p = 0.038). Conclusions Results suggest that treatment intensification is often delayed despite consistently poor glycaemic control for more than 12 months, contrary to treatment guideline recommendations. Findings from this study highlight that some T2DM patients may benefit from more rapid treatment intensification, which could improve glycaemic control and reduce the risk for many short- and long-term health complications.